O Processo de Alinhamento Estratégico Organizacional: um Estudo Multicaso no Setor Metalmecânico Agrícola - Giovani André Plentz (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2005)
This study it identifies as the corporative organizational strategies are defined and as the process of strategically alignment in the organizational context from the perception of the managers occurs, in industries of great transport of the segment northwestern agricultural metal-mechanic of the State of the Rio Grande do Sul. To give it has supported to the study was considered: (1) to identify the forms to establish the strategies in the scope of the directive cupola; (2) to identify to the process of unfolding and communication of the corporative strategies in the management process; e (3) to present critical factors and of success in the process of unfolding of the strategies from methodologies and of systems of information of support to the management in the process of organizational strategically alignment. In terms of the used methodology, one is about a study multiin case that, fit in the characteristics of the qualitative boarding. The procedures technician had involved descriptive studies, documentary research and interviews half-structuralized with the managers. Of analysis of processes of alignments strategically concluded on one constructo theoretician that demonstrates to the involved elements in the processes of alignments and a model of strategically alignment for each searched company, who evidences the form as these companies elaborate the strategies, as they is unfolded and the relations established with the managers. Amongst the contributions, they deserve prominence: (1) the proposal of one constructo theoretician who assists in the analysis of the effectiveness of the strategically alignment; (2) it offers of a model of strategically alignment for each organization study object, that systemize its process of conception and unfolding of the strategies; (3) a set of theoretical inferences resultant of the carried through analysis that helps to enrich the study of the organizational strategically alignment; e finally, (4) bigger knowledge on the form as these companies develops its power to decide process, allowing a reflection on adopted systematic.